DC voltage stabilization method and system for active power factor correction of charging module - YE QUANHAI; LI SHUNZHANG; XU JIN; HE CHAO; LIU XIAOWEI (2017)
The invention discloses a DC voltage stabilization method and a system for the active power factor correction of a charging module. The method comprises the following steps of outputting a reactive power to an AC power grid by an active power factor correction device, detecting the A-phase voltage Ua of the three-phase AC power grid, and acquiring a vector U1 perpendicular to the A-phase voltage Ua; according to Qload and delta Udc, carrying out the fuzzy reasoning to obtain a coefficient K, wherein Qload represents the reactive power of a load for receiving reactive compensation, and delta Udc represents the difference value between the capacitance reference voltage Uref of the active power factor correction device and the capacitance actual voltage Udc of the active power factor correction device; calculating U2 according to the formula of U2=K*U1; carrying out matrix operation by utilizing the reactive current iq of the load for receiving the reactive compensation and the U2 to obtain a matrix I*; absorbin